2000
DOI: 10.1128/jb.182.17.4773-4782.2000
|View full text |Cite
|
Sign up to set email alerts
|

Native Corrinoids fromClostridium cochleariumAre Adeninylcobamides: Spectroscopic Analysis and Identification of Pseudovitamin B12and Factor A

Abstract: The corrinoids from the obligate anaerobe Clostridium cochlearium were extracted as a mixture of Co ␤ -cyano derivatives. From 50 g of frozen cells, approximately 2 mg (1.5 mol) of B 12 derivatives was obtained as a crystalline sample. Analysis of the corrinoid sample of C. cochlearium by a combination of high-pressure liquid chromatography and UV-Vis absorbance spectroscopy revealed the presence of three cyano corrinoids in a ratio of about 3:1:1. The spectroscopic data acquired for the sample indicated the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 67 publications
1
61
0
1
Order By: Relevance
“…Although LPG3 grazes on these cyanobacterial species that robustly produce pseudocobalamin, its requirement for heterotrophic bacteria that produce cobalamin suggests that it has specificity for cobalamin and cannot utilize pseudocobalamin. While pseudocobalamin is produced by many bacterial species, including cyanobacteria (19), Lactobacillus reuteri (43), and Clostridium cochlearium (44), other eukaryotes that utilize corrinoids also have specificity for cobalamin over pseudocobalamin. The human intrinsic factor protein binds cobalamin and facilitates absorption across the small intestine and has specificity for cobalamin over pseudocobalamin (45).…”
Section: Discussionmentioning
confidence: 99%
“…Although LPG3 grazes on these cyanobacterial species that robustly produce pseudocobalamin, its requirement for heterotrophic bacteria that produce cobalamin suggests that it has specificity for cobalamin and cannot utilize pseudocobalamin. While pseudocobalamin is produced by many bacterial species, including cyanobacteria (19), Lactobacillus reuteri (43), and Clostridium cochlearium (44), other eukaryotes that utilize corrinoids also have specificity for cobalamin over pseudocobalamin. The human intrinsic factor protein binds cobalamin and facilitates absorption across the small intestine and has specificity for cobalamin over pseudocobalamin (45).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they cannot use Cbi as a source of corrinoids. When provided with CN-pseudo-B 12 (16), this strain grew using ethanolamine as the sole carbon source. Pseudo-B 12 must therefore serve as an alternative to cobalamin and allow activity of ethanolamine ammonia lyase.…”
Section: Conditions That Prevent Synthesis or Installation Of Any ␣-Amentioning
confidence: 99%
“…1) include the base 5,6-dimethylbenzimidazole (DMB) as an ␣-axial ligand. Prokaryotes, the only producers of vitamin B 12 , make "complete" corrinoid cofactors with a variety of alternative ␣-axial ligands, including benzimidazoles, phenols, and purines (16,52). These alternative corrinoids may be functional equivalents of coenzyme B 12 for many bacterial enzymes, but functional differences are suggested by the selectivity of the human assimilatory protein, intrinsic factor for cobalamin, the DMB-containing vitamin B 12 (53).…”
mentioning
confidence: 99%
“…Several recent reports have shown that pseudo-B 12 is the dominant corrinoid produced by the anaerobes Clostridium cochlearium (9) and Lactobacillus reuteri (24), the cyanobacteria Nostoc commune (32) and Aphanizomenon flos-aquae (17), and the alga Aphanothece sacrum (31). Historically, these corrinoids have been viewed as "alternate" forms.…”
mentioning
confidence: 99%